2022
DOI: 10.3390/nano12213812
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol as Additive to Achieve N-Conductive Melt-Mixed Polymer/Carbon Nanotube Composites for Thermoelectric Application

Abstract: The development of thermoelectric (TE) materials based on thermoplastic polymers and carbon nanotubes is a focus of current TE research activities. For a TE module, both p- and n-conductive composites are required, whereby the production of n-conductive materials is a particular challenge. The present study investigates whether adding polyethylene glycol (PEG) as n-dopant during the melt-mixing of the conductive composites based on polycarbonate, poly(ether ether ketone), or poly(butylene terephthalate) with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…To overcome the problems with PVP, polyethylene glycol (PEG) is a suitable alternative additive for n-doping in polymer/SWCNT composites. It was shown that for PP [ 5 ] as well as PC, PBT, and PEEK [ 18 ] based composites with SWCNTs the addition of PEG leads to negative Seebeck coefficients. Unfortunately, only Luo et al [ 5 ] investigated the long-term stability after 8 months of storage in air.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To overcome the problems with PVP, polyethylene glycol (PEG) is a suitable alternative additive for n-doping in polymer/SWCNT composites. It was shown that for PP [ 5 ] as well as PC, PBT, and PEEK [ 18 ] based composites with SWCNTs the addition of PEG leads to negative Seebeck coefficients. Unfortunately, only Luo et al [ 5 ] investigated the long-term stability after 8 months of storage in air.…”
Section: Discussionmentioning
confidence: 99%
“…After cooling down, the obtained extruded strands were compression molded into plates (60 mm diameter, 0.5 mm thickness) using the hot press PW40EH. The preparation conditions for melt compounding and compression molding are described in Krause et al [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations